A bibliometric approach to Revista de Comunicación (Peru) since 2002 to 2019 - Estrada-Cuzcano, Alonso (2020)
This article presents a visibility and scientific impact analysis based on papers published by Revista de Comunicación since 2002 to 2019. Bibliometric methods used included approach at author-level (Lotka, collaboration index), article-level (co-occurrence) and journal-level (h-index, citations). Also, Scopus, Web of Science and Google Scholar were used as citation data sources, Publish or Perish and VOSviewer as analysis tools. Results shows an optimal performance from Revista de Comunicación that evidences its best positioning between indexed serial publications from Latin America and Spain wich integrate a select group of scholarly journals in communication.